On the Basic Extraction Properties of a Phenyl Trifluoromethyl Sulfone-Based GANEX System Containing CyMe4-BTBP and TBP. Issue 4 (7th June 2018) - Halleröd, Jenny; Ekberg, Christian; Authen, Thea; Bertolo, Laura; Lin, Mu; Grüner, Bohumír; Švehla, Jaroslav; Wagner, Christoph; Geist, Andreas; Panak, Petra; Aneheim, Emma
ABSTRACT: A Grouped ActiNide EXtraction (GANEX) process for the extraction of actinides from used nuclear fuel for transmutation purposes has been investigated. The studied solvent consists of phenyl trifluoromethyl sulfone (FS-13), CyMe4 -BTBP, and TBP, a combination that has previously shown promising results. The time to reach extraction equilibrium for the system has been found to be less than 20 min. A 2:1 complex has been found between CyMe4 -BTBP and americium(III) or curium(III), whereas plutonium(IV) and CyMe4 -BTBP create a 1:1 complex. The extraction of fission product is low in the system.